The Avoidable War: The Dangers of a Catastrophic Conflict between the US and Xi Jinping’s China (Journal of Contemporary Studies, 2022)
The strategists and policymakers predict that the 2020s will be “the decade of living dangerously” due to the unfolding crisis in the relationship between the United States (US) and China. The former Prime Minister of Australia, Kevin Rudd (2007-2010 and 2013), in his book “The Avoidable War: The Dangers of a Catastrophic Conflict between the US and Xi Jinping’s China” terms it a “decisive decade” in the dynamics of changing balance of power between China and the US.